Knockdown of ANGPTL-4 inhibits inflammatory response and extracellular matrix accumulation in glomerular mesangial cells cultured under high glucose condition - Linfang Qin; Ruimin Zhang; Suxia Yang; Fang Chen; Jun Shi (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Diabetic nephropathy (DN) is one of the major diabetic complications that lead to end-stage renal failure. Angiopoietin-like protein-4 (ANGPTL-4) has been reported to be dysregulated in diabetes mellitus and diabetic complications. However, the role of ANGPTL-4 in glomerular mesangial cells (MCs) during DN remains unclear. In the present study, we evaluated the role of ANGPTL-4 in MCs in response to high glucose (HG) condition and the potential mechanism. The results proved that ANGPTL-4 expression is significantly increased in HG-stimulated MCs. Knockdown of ANGPTL-4 suppressed HG-induced cell proliferation of MCs. The production of pro-inflammatory cytokines including TNF-α, IL-1β, IL-6 were decreased in ANGPTL-4 knocked down MCs. Inhibition of ANGPTL-4 markedly suppressed the expressions of extracellular matrix (ECM) proteins, collagen IV (Col IV) and fibronectin (FN), in HG-stimulated MCs. Furthermore, ANGPTL-4 knockdown inhibited the HG-induced activation of NF-κB signaling pathway in MCs. Collectively, knockdown of ANGPTL-4 suppressed HG-induced cell proliferation, inflammatory response, and ECM accumulation inhibiting NF-κB signaling pathway in MCs. These findings suggested that ANGPTL-4 might be a therapeutic target for the prevention and treatment of DN.